Oxygen Scavenging Effect of LaLuO3/TiN Gate Stack in High-Mobility Si/SiGe/SOI Quantum-Well Transistors*Supported by the National Natural Science Foundation of China under Grant No 61306126. (May 2016) - Feng 冯, Jin-Feng 锦锋; Liu 刘, Chang 畅; Yu 俞, Wen-Jie 文杰; Peng 彭, Ying-Hong 颖红
Abstract : Higher-κ dielectric LaLuO3, deposited by molecular beam deposition, with TiN as gate stack is integrated into high-mobility Si/SiGe/SOI quantum-well p-type metal-oxide-semiconductor field effect transistors. Threshold voltage shift and capacitance equivalent thickness shrink are observed, resulting from oxygen scavenging effect in LaLuO3 with Ti-rich TiN after high temperature annealing. The mechanism of oxygen scavenging and its potential for resistive memory applications are analyzed and discussed.